2019
DOI: 10.1016/j.ypmed.2019.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive resources moderate the adverse impact of poor perceived neighborhood conditions on self-reported physical activity of older adults

Abstract: Poor neighborhood conditions are associated with lower levels of physical activity for older adults but socio-ecological models posit that physical activity depends on both environmental and individual factors. Older adults' ability to overcome environmental barriers to physical activity may partially rely on cognitive resources. However, evidence on the moderating role of these cognitive resources in the associations between environmental barriers and physical activity is still lacking. We analyzed cross-nati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 46 publications
(60 reference statements)
1
42
1
Order By: Relevance
“…The outdoor environment has a large impact on the behavior of residents. Research has pointed out that poor neighborhood conditions are associated with lower levels of physical activity among older adults [43]. One study examined the effect of food retail on the physical activity of adolescents and found that the availability of food stores within walking distance increased their physical activity levels [44].…”
Section: Discussionmentioning
confidence: 99%
“…The outdoor environment has a large impact on the behavior of residents. Research has pointed out that poor neighborhood conditions are associated with lower levels of physical activity among older adults [43]. One study examined the effect of food retail on the physical activity of adolescents and found that the availability of food stores within walking distance increased their physical activity levels [44].…”
Section: Discussionmentioning
confidence: 99%
“…22 Poor environmental factors such as neighborhood conditions also increase the odds of being physically inactive 23 , but higher cognitive resources reduce this adverse influence. 24…”
Section: Etiologymentioning
confidence: 99%
“…Hastings and Snowden (2019) measure neighbourhood disadvantage solely using variables depicting social disorder and lack of amenities. Cheval et al (2019) in the large European study SHARE used subjective assessments of service availability and estimations of neighbourhood nuisances, such as pollution, vandalism, crime and the like.…”
Section: The Use Of Subjective and Process Indicators In Measuring Deprived Communitiesmentioning
confidence: 99%